SUMBANGSIH ILMUWAN ISLAM PADA IPTEK - Dede Rubai Misbahul Alam; Raudhatul Islamiyah; Qisthy Amiroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the contributions of Muslim scholars to the development of science and technology from the medieval period to the modern era, the intellectual learning traditions that supported scientific advancement, and the factors contributing to the decline of scientific productivity in the Muslim world. Using a qualitative descriptive and historical approach, this research analyzes the roles of prominent Muslim figures such as Ibn al-Haytham in optics, Al-Khawarizmi in mathematics, Al-Zahrawi in medicine, Al-Farabi in philosophy, as well as modern scientists including Abdus Salam, Ahmed Zewail, and Maryam Mirzakhani. The results indicate that Islamic civilization played a significant role in establishing the foundations of modern science through rational, empirical, and systematic methodologies rooted in the Islamic worldview, which integrates faith, ethics, and knowledge. Scientific activities were understood as acts of worship aimed at achieving human welfare. However, the decline of Muslim scientific contributions was influenced by political instability, weakened educational institutions, intellectual stagnation, colonial domination, the dichotomy between religious and secular sciences, and the limited development of research culture. This study highlights the importance of revitalizing an integrative and ethical Islamic scientific tradition to strengthen the development of science and technology within contemporary Islamic education.